A Systematic Mapping of Configuration Management Activities in Software Product Line - Espinel Mena, Gonzalo P. (2024)
In the software product line (SPL), configuration management (CM) is a multidimensional problem that is taking great attention in software development. Although much research has been developed on this topic, there is no clear view of the current state of it. In this study, we used a systematic method to develop a map of configuration management across product lines to classify relevant literature. The resulting map provides an overview of this research through the identification of the main activities of the CM, the types and trends of research as well as the maturity of existing contributions. Because the CM in SPL is still in its formative stage, we believe that this work will contribute to the process of providing a more common and coherent conceptual basis for its understanding. In addition, it can help to detect important research problems and gaps.